Hemorrhage complications in obstetric antiphospholipid syndrome: Risk factors and association with adverse pregnancy outcomes - Yongjing Luo; Jiayang Jin; Jiayang Jin; Yani Yan; Mengyao Zhang; Mengyao Zhang; Lei Hou; Yuke Hou; Yuke Hou; Qiuyan Pei; Chun Li; Chun Li (Frontiers in Immunology, 2023)
BackgroundBleeding complications are recognized as relatively infrequent manifestations of antiphospholipid syndrome (APS), and the safety of antithrombotic therapy during pregnancy is of concern. This study aims to assess the risk factors and possible associations between bleeding complications and adverse pregnancy outcomes (APOs) in patients with APS.MethodsA retrospective cohort study was conducted at the Peking University People’s Hospital. The clinical and immunologic features, bleeding complications, treatment, and pregnancy outcomes of patients with APS were collected. Univariate and multivariate logistic regression analyses were applied to assess the associations between APOs and bleeding complications.ResultsA total of 176 participants with obstetric APS were included in the analysis. There were 66 (37.50%) patients with APS with hemorrhage complications and 86 (48.86%) patients with APS with APOs. Mucocutaneous hemorrhage was associated with APOs including fetal death after 12 weeks [odds ratio (OR) = 10.73, 95% confidence interval (CI): 1.61–71.74, p = 0.014], preterm delivery prior to 34 weeks (OR = 8.30, 95% CI: 2.31–29.84, p = 0.001), and small for gestational age (OR = 4.17, 95% CI: 1.22–14.21, p = 0.023) in univariate logistic regression analyses. It also independently associated with preterm delivery prior to 34 weeks (OR = 40.29, 95% CI: 1.45–1121.32, p = 0.030) in multivariate logistic regression analyses. Receiver operating characteristic (ROC) analysis evaluating the accuracy of these factors for preterm delivery prior to 34 weeks showed that the area under ROC curve was 0.871.ConclusionThe study shows that mucocutaneous hemorrhage may be an indication of the occurrence of APOs in obstetric patients with APS.